When I Means We: A Reading of School in French Caribbean Apprenticeship Novels - Pascale De Souza (Studies in 20th & 21st Century Literature, 2002)
While most critics agree that the quest for identity which underlies much of post-colonial literature is illustrated in the thematic approaches adopted by writers, this study further the argument by suggesting that it also conditions writers' selection of narrative strategies. In its representation of subjectivity in process, the apprenticeship novel seems to offer an enticing model of self-completion. This narrative strategy, however, presents particular complexities when used to portray coming of age in a society divided along ethnic lines. Simon Gikandi argues with regards to the Caribbean that the probability of a quest for identity reaching fruition is nil, but other critics take a more hopeful stand when they see the apprenticeship novel as a "novel of initiation into the methods of survival in a context marked by 'the presence of the Other'" (Kandé 34; my emphasis). The acquisition of the French language and reading and writing skills through school offers a salient example of these opposite stands. An analysis of several French Caribbean novels which explore the role of school reveals the emergence of a rift as school enables young characters such as José in La Rue Cases-Nègres by Joseph Zobel or the narrator and her brother in Le Temps des Madras by Françoise Ega to achieve a certain measure of wholeness, but becomes a deadly lure for young girls such as Zétou in Le Quimboiseur l'avait Dit or Mélanée in Pluie et Vent sur Télumée-Miracle. Though the rift often follows gendered lines, it is predominantly attributable to the existence, or lack thereof, of a strong support system which enables characters to retain their Caribbean identity while acquiring the skills needed to function in a French-speaking world.
Keywords: quest for identity; identity; post-colonial; post-colonial literature; narrative strategies; self-completion; ethnic lines; Simon Gikandi; Caribbean; the other; novel; Kandé; acquisition of the French language; reading; writing; salient; French Caribbean novels; school; Le Temps des Madras; Françoise Ega; young girls; Zétou; Le Quimboiseur l& #x27; avait Dit; Mélanée; Pluie et Vent sur Télumée-Miracle; gendered lines; gender; Caribbean identity; French-speaking; French-speaking world